The role of angiogenic factors in the management of preeclampsia. - Flint, E; Cerdeira, A; Redman, C; Vatish, M (Obstetrics and Gynaecology, 2019)
Preeclampsia is a pregnancy disorder causing substantial maternal and fetal morbidity and mortality. In the UK, its diagnosis currently depends upon new onset hypertension and proteinuria. There is a clinical need for enhanced screening to prevent unnecessary resource use and improve outcomes. Here, the current practice in preeclampsia diagnosis will be summarized, with assessment of the evidence that angiogenic factors could improve its management. Although the combination of new onset hypertension and proteinuria define and hence diagnose the disorder, separately they are poorly predictive. Preeclampsia is ultimately a placental disease caused by syncytiotrophoblast dysfunction. The angiogenic factors placental growth factor, soluble fms-like tyrosine kinase 1 and soluble endoglin, all originating at least in part from the syncytiotrophoblast, are biomarkers with predictive potential for preeclampsia and related adverse outcomes. Recent work with the soluble fms-like tyrosine kinase 1/placental growth factor ratio has identified key measurement cutoffs, with one having a high negative predictive value for preeclampsia. The soluble fms-like tyrosine kinase 1/placental growth factor ratio seems particularly promising as a screening measure, able to predict accurately the short-term absence of preeclampsia and suggest the likelihood of adverse events within 4 weeks. The ratio could be used to allocate specific management plans to patients according to risk. An understanding of angiogenic factors may also lead to new therapeutic options for a condition currently only curable by delivery, although it must be remembered that the factors are markers of underlying syncytiotrophoblast stress, which would not be resolved by targeting them.